The prognostic outcomes of acute myocardial infarction stratified according to metabolic health and obesity status. (3rd October 2022) - Chew, N; Kong, G; Ng, C H; S, V; Chin, Y H; Muthiah, M Y; Khoo, C M; Chai, P H; Foo, R; Chan, M Y; Loh, P H
Abstract: Background: There has been emerging evidence on the favourable cardiovascular disease incidence in non-obese subjects with healthy metabolism. However, little is known regarding the prognosis across the metabolic phenotypes once cardiovascular disease is established. This study examines the prognosis of patients with acute myocardial infarction (AMI) stratified according to metabolic health and obesity status. Methods: A retrospective study conducted in a tertiary hospital between 2014–2021. Consecutive patients with AMI were allocated into 4 groups based on metabolic and obesity profile: metabolically healthy obesity (MHO), metabolically healthy non-obesity (MHNO), metabolically unhealthy obesity (MUO) and metabolically unhealthy non-obesity (MUNO). The primary outcome was all-cause mortality. Cox regression examined the independent association between mortality and metabolic phenotypes, adjusting for age, sex, AMI type and ejection fraction. Results: A total of 9958 patients were studied with majority (68.5%) in the MUNO group, followed by MUO (25.1%), MHNO (5.6%), and MHO (0.8%). MHO patients had lowest mortality (7.4%), followed by MHNO (9.7%), MUO (19.2%) and MUNO (22.6%, p<0.001). Relative to MHNO, MUO (HR 1.610, 95% CI 1.198–2.163, p=0.002) and MUNO (HR 1.383, 95% CI 1.043–1.835, p=0.024) had significantly higher mortality risk, but not MHO (HR 1.514, 95% CI 0.649–3.534, p=0.337), after adjusting for confounders. Kaplan-Meier curves showed favourable survival in metabolically healthy groups with clear divergence from metabolically unhealthy groups (p<0.001). There were stepwise increments in mortality with increasing number of metabolic risk factors regardless of obesity status (p<0.001). Favourable survival was observed in overweight and obese versus normal weight patients regardless of metabolic health. Conclusion: Metabolically healthy AMI patients had favourable prognosis compared to metabolically unhealthy patients. The obesity paradox was observed in the AMI cohort, but the beneficial effects of obesity appeared not as pronounced in magnitude as in metabolically healthy groups. Funding Acknowledgement: Type of funding sources: None.